Strategi Musik dan Kerygma Influencer Kristen dalam Membangun Gambar Diri Native Digital - Joni Manumpak Parulian Gultom; Manahan Uji Simanjuntak; Ester Lina Situmorang; Ronald Sianipar; Septerianus Waruwu (Sekolah Tinggi Teologi Torsina Surakarta, 2021)
The advancement of the virtual world has shaped the millennial generation and beyond to become digital natives who are out of control, without obstacles, and connected. The global world is presented freely with negative values of life, absurd, meaningless, and seemingly without God. The emphasis is on how to rebuild this fallen, weak, and chaotic native digital self-image. The goal is that through music and kerygma strategies, these Christian influencers can become a catalyst for the digital generation to return to God with the proper self-image. So it is an essential solution because the virtual space has a vast scope, without limits and high flexibility after church services have begun to be abandoned. A research method is a qualitative approach with data collection through literature study and observation. It is hoped that through this research: (1)New Christian influencers will emerge with spiritual content, (2)The millennial generation will repent and recover, (3)So that they will return and be integrated with the church. Future research is expected to be quantitative to see how strong the influence of changes and new strategies can be as alternative solutions.